An Americium‐Containing Metal–Organic Framework: A Platform for Studying Transplutonium Elements. Issue 46 (30th September 2019) - Ridenour, J. August; Surbella, Robert G.; Gelis, Artem V.; Koury, Daniel; Poineau, Frederic; Czerwinski, Kenneth R.; Cahill, Christopher L.
Abstract: The synthesis, structure, and spectroscopic characterization of the first transplutonium metal–organic framework (MOF) is described. The preparation and structure of Am‐GWMOF‐6, [Am2 (C6 H8 O4 )3 (H2 O)2 ][(C10 H8 N2 )], is analogous to that of the isostructural trivalent lanthanide‐only containing material GWMOF‐6. The presented MOF architecture is used as a platform to probe Am 3+ coordination chemistry and guest‐enhanced luminescent emission, whereas the framework itself provides a means to monitor the effects of self‐irradiation upon crystallinity over time. Presented here is a discussion of these properties and the opportunities that MOFs provide in the structural and spectroscopic study of actinides. Abstract : The first transplutonium metal–organic framework (MOF), containing the trivalent actinide americium ([Am2 (C6 H8 O4 )3 (H2 O)2 ]⋅(C10 H8 N2 )), is presented as Am‐GWMOF‐6, a structurally analogous compound to that of the trivalent lanthanide‐only containing material GWMOF‐6. The presented MOF architecture is used as a platform to probe Am 3+ coordination chemistry and guest‐enhanced luminescent emission.